RegeneraÇÃo natural do componente arbÓreo apÓs a mortalidade de um maciÇo de taquara em um fragmento de floresta ombrÓfila mista em lages - SC - Dos Santos, Kristiana Fiorentin; De Souza Ferreira, Tiago; Higuchi, Pedro; Da Silva, Ana Carolina; Vandresen, Paula Búrigo; Da Costa, Adriano; Spada, Grasiela [UNESP]; Schmitz, Verônica; De Souza, Franciele (My University, 2015)
The present study aimed to analyze the floristic and structural descriptors of tree species natural regeneration in a forest sector with synchronized bamboo (Merostachys multiramea Hackel) die-off (CT) and an adjacent area with continuous canopy cover (ST) in an araucaria forest fragment in the municipality of Lages, Santa Catarina state. A total of 14, 5x5m, plots (six plots in CT sector and eight in ST sector) were allocated, where all tree species regenerative individual with circumference at breast height smaller than 15cm and height higher than 25cm was measured (diameter at soil level) and identified. The richest families were: Myrtaceae (nine), Solanaceae (six) and Aquifoliaceae (four). The Shannon Diversity Index in ST and CT sectors were respectively 2.73 and 2.31. The species with the highest importance values in CT sector were Solanum variabile, Piptocarpha angustifolia, Mimosa scabrella, Jacaranda puberula and Solanum pseudoquina. In ST sector, the species with highest importance values were Myrsine lorentziana, Casearia decandra, Cinnamodendron dinisii, Drimys brasiliensis and Ilex paraguariensis. The results showed that the synchronized bamboo die-off influenced the spatial variation in the floristic and structural descriptors of the tree species natural regeneration.
Tree species natural regeneration after a massive bamboo die-off in an araucaria forest fragment in lages, santa catarina state
Keywords: Merostachys multiramea; Phytosociological descriptors; Regenerative component